Pengaruh Citra Merek dan Kualitas Produk Terhadap Kepuasan Pelanggan Restoran Eatlah Ho Chick Minh - Pieter; Anjar Dwi Astono (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of brand image and product quality on consumer satisfaction of EATLAH Ho Chick Minh Restaurant. In this study, there are three variables in this study, namely Brand Image, Product Quality and Customer Satisfaction. Researchers used quantitative methods and the sample used in this study amounted to 145 respondents who were customers of EATLAH Ho Chick Minh Restaurant. The technique used in this research is purposive sampling. The research data analyzed shows that the Brand Image variable has a significant effect on Customer Satisfaction, the Product Quality variable has a significant effect on Customer Satisfaction and the Brand Image and Product Quality variables together have a significant effect on Customer Satisfaction.